Free Radical Scavenging Properties and Induction of Apoptotic Effects of FA Fraction Obtained after Proteolysis of Bioactive Peptides from Microalgae Synechococcus sp. VDW - Rutairat Suttisuwan; Saranya Phunpruch; Tanatorn Saisavoey; Papassara Sangtanoo; Nuttha Thongchul; Aphichart Karnchanatat (My University, 2019)
This study aims to determine the antioxidant activity of bioactive peptides derived from Synechococcus sp. VDW cells cultured for 21 days. Synechococcus sp. VDW protein hydrolysates were prepared with trypsin and purified by ultrafiltration with molecular mass cut-off membranes of 10, 5 and 3 kDa. The M<3 kDa (FA) fraction had the highest 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and 2,2'-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activities, with IC50 values of (11.5±0.3) and (13.6±0.2) µg/mL, respectively. The FA fraction was separated by reversed phase HPLC to yield four subfractions (F1-4). The F4 subfraction showed the highest maximum ABTS radical scavenging activity (3.55±0.61) % and it was selected for further analysis by electrospray ionisation quadrupole time-of-flight mass spectrometry (ESI-Q-TOF-MS/MS) based on de novo peptide sequencing. Five antioxidant peptides were identified, of which AILESYSAGKTK had the highest ABTS radical scavenging activity. Furthermore, the FA fraction showed high cytotoxic activities against human cancer-derived cell lines, especially the colon cancer cell line (SW620) with an IC50 value of (106.6±21.5) µg/mL, but not the untransformed Wi38 cell line. The FA fraction activated the apoptotic pathway in SW620 cells after treatment for 24, 48 and 72 h, with the highest activities of caspases-3, -8 and -9 being observed after treatment for 72 h. These findings suggested that microalgae Synechococcus sp. VDW may be used to develop natural anticancer drugs.
Keywords: ABTS; Ultrafiltration (renal); Protein Hydrolysis and Bioactive Peptides